Oxygen uptake kinetics and time to exhaustion in cycling and running: A comparison between trained and untrained subjects - Caputo, F. [UNESP]; Mello, M. T.; Denadai, B. S. [UNESP] (Taylor & Francis, 2003)
The objective of the present study was to compare pulmonary gas exchange kinetics (VO 2 kinetics) and time to exhaustion (Tlim) between trained and untrained individuals during severe exercise performed on a cycle ergometer and treadmill. Eleven untrained males in running (UR) and cycling (UC), nine endurance cyclists (EC), and seven endurance runners (ER) were submitted to the following tests on separate days: (i) incremental test for determination of maximal oxygen uptake (VO 2max) and the intensity associated with the achievement of VO 2max (IVO 2max) on a mechanical braked cycle ergometer (EC and UC) and on a treadmill (ER and UR); (ii) all-out exercise bout performed at IVO 2max to determine the time to exhaustion at IVO 2max (Tlim) and the time constant of oxygen uptake kinetics (τ). The τ was significantly faster in trained group, both in cycling (EC = 28.2 ± 4.7 s; UC = 63.8 ± 25.0 s) and in running (ER = 28.5 ± 8.5 s; UR = 59.3 ± 12.0 s). Tlim of untrained was significantly lower in cycling (EC = 384.4 ± 66.6 s vs. UC; 311.1 ± 105.7 s) and higher in running (ER = 309.2 ± 176.6 s vs. UR = 439.8 ± 104.2 s). We conclude that the VO 2 kinetic response at the onset of severe exercise, carried out at the same relative intensity is sensitive to endurance training, irrespective of the exercise type. The endurance training seems to differently influence Tlim during exercise at IVO 2max in running and cycling. © 2003 Taylor & Francis Ltd.
Keywords: Aerobic training; Cycling; Maximal aerobic exercise; Oxygen uptake kinetics; Running; oxygen; athlete; bicycle ergometer; cycling; exercise; exhaustion; human; human experiment; kinetics; lung gas exchange; male; normal human; oxygen consumption; physical stress; running; training; treadmill; Adaptation, Physiological; Adult; Bicycling; Exertion; Humans; Kinetics; Male; Oxygen Consumption; Physical Endurance; Physical Fitness; Time Factors